The History of Slavery in Indonesia Through The Lens of Karl Marx's Political Economy Theory - Monady, Hanief; Mobarak, Najih Fathi El (Prodi Ilmu Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, 2025)
This research explores the historical development of slavery in Indonesia through Karl Marx’s Political Economy theory. It traces the evolution of slavery from the pre-colonial to post-colonial periods and its impact on Indonesia’s social, economic, and political structures. Using Marx’s perspective, the study reveals how slavery was shaped by capitalist economic systems that enabled exploitation, particularly during the colonial era. It emphasizes the connection between slavery and class conflict, where capital owners benefited from the labor of oppressed slaves. The study also highlights various forms of resistance against this exploitative system. By examining these historical dynamics, the research offers a deeper understanding of the roots of social and economic inequality in Indonesia. It contributes to broader discussions on social justice by showing how political-economic systems influenced oppression. Additionally, this research serves as a foundation for developing effective policies to combat modern slavery and promote social welfare. Ultimately, it stresses the importance of addressing structural inequalities to achieve justice and equality in contemporary Indonesian society.